E-Commerce in Malaysia From Law Perspective - Thorique Akbar Nasution (Mahadi: Indonesia Journal of Law, 2023)
The study demonstrates a correlation between the law in e-commerce consumer sale of goods with competition law, consumer welfare, and e-commerce. Because the existing underlying competition law theory is exclusively based on economic theory, there are several challenges in presenting some indicators of the distinct market of e-commerce for consumer sales of goods and using consumer welfare-based consumerism that promotes social justice and equity. The most important part of the e-commerce system, process, and structure is aided by highly advanced technological innovation from all supply, distribution, and information exchange processes towards the demand chain, which is the consumers. There are several dimensions with distinct stakeholders and actors at various levels to enable, support, perform, and produce multiple income streams from e-commerce. Sales of customer data often occur in e-commerce competition. This results in inconvenience to consumers who have transacted at an online store. Competition law needs to be tightened in order to provide comfort from the customer and seller side.